SUSTAINABLE LEADERSHIP KEY FACTORS: STUDY ON PROFIT AND NON PROFIT ORGANISATIONS IN BATAM INDONESIA - Willy Candra; Didi Sundiman (Jurnal Manajemen dan Kewirausahaan, 2020)
The purpose of this study is to examine the main factors forming sustainable leadership in organizations. The sampling method of this study was simple random sampling, which got as many as 289 employees or members of organizations in the city of Batam. Principal Component Analysis is used in the process of analyzing the data of this study using statistical programming tools in R and RStudio. The results of this study are the Sustainability Leadership of Human Resources in the organization formed by 4 factors, namely factor 1- Harmony Leadership, factor 2- Ethical Leadership, factor 3- Personal value Leadership and factor 4- Care Leadership.